Decision knowledge triggers in continuous software engineering - Kleebaum, Anja; Paech, Barbara (2018 ACM/IEEE 4th International Workshop on Rapid Continuous Software Engineering (RCoSE 2018), 2018)
Decision knowledge encompasses decisions and related information such as the problems the decisions address, their rationale, or alternatives. The management of decision knowledge is considered important for software development, however, it is often not integrated, since it requires additional effort and developers do not perceive short-term benefits. Continuous software engineering offers new possibilities to overcome these drawbacks: During continuous software engineering, developers perform practices suitable to integrate the management of decision knowledge in their daily work. For example, developers regularly commit code and manage tasks to implement features. In this paper, we present ideas on how to trigger the developers to capture and use decision knowledge during these practices, in particular to 1) package distributed decision knowledge, 2) make tacit decisions explicit, and 3) consider consistency between decisions.